Laws of the State of New-York, Relating to the City of Schenectady 58 (1824) - (:unkn) unknown (My University, 1824)
A Law to prevent injuries by fire, and for other purposes, § XI: That if any person shall fire or discharge any gun, pistol, rocket, cracker, squib or other fire works, in any street, lane or alley, or in any yard, garden or other enclosure, or in any place which persons frequent to walk within the limits aforesaid, without permission of the mayor or one of the aldermen or assistants of this city, such person shall forfeit for every such offence the sum of one dollar...
Keywords: DISCHARGE